The Qur'an, translation and the media: a narrative account - Elimam, Ahmed Saleh (Routledge advances in translation and interpreting studies, 2022)
Introduction -- Translating the Qur'an in the Press Media -- Narrative Theory and Methodology -- British Press Media Coverage of Islam -- Italian Press Media Coverage of Islam -- Spanish Press Media Coverage of Islam -- Discussion: Popular Narratives and Narrative Tools -- Conclusion.